Peningkatan Kompetensi Guru Produktif SMK: Pengembangan Video Interaktif dengan Aplikasi Capcut - Liah Siti Syarifah; Widia Murni Wijaya; Yayah Rahyasih; Fenty Setiawati; Rulli Nasrullah (Jurnal Surya Masyarakat, 2025)
This community service activity aims to improve the knowledge and skills of Productive Teachers in Vocational High Schools in creating varied digital learning resources, especially interactive learning videos. Seminars, training, and mentoring activities were carried out on November 16-30, 2024 at Tunas Unggul School. Through a series of stages including planning, implementing seminars, workshops and mentoring and evaluation, the results showed a significant increase in teachers' understanding and skills regarding interactive learning videos. Teachers are able to integrate technology into learning effectively, in order to support the implementation of the Merdeka Curriculum. This is based on the results of the pre-test and post-test, namely the average score at the time of the pre-test was 70.40 and at the time of the post-test it increased by 89.60. This means that there has been a change and increase in participants' understanding of interactive learning videos. Furthermore, the N Gain Score of 0.67 is in the moderate category with a percentage of 66.67% which shows that community service activities in the form of seminars, training and mentoring have been quite effective. Furthermore, the results of the satisfaction questionnaire also showed that 92% of participants stated that the activities were carried out very well. Therefore, the sustainability of this program needs to be pursued through additional mentoring and training. This activity emphasizes the importance of a needs-based approach, ongoing support, and effective collaboration to help teachers improve the skills they need in the learning process that leads to improving the quality of education.